Analysing and Mapping Cited Works: Citation Behaviour of Filipino Faculty and Researchers - Eclevia, Marian Ramos; Janio, Rizalyn V. (Qualitative and Quantitative Methods in Libraries; Vol 5 No 2 (2016): June 2016 Issue, 2017)
Scholarly literature on citation studies has focused on understanding the relationship of two articles through citations and measurement of citation counts of an article; thus, citation behaviour in a simplified, linear relationship. Citing of sources involves complex behaviours which are influenced by a variety of subjective factors. This study identifies and describes the citing behaviours of faculty members of Ateneo De Manila University, De La Salle University, and University of the Philippines. Using ISI Web of Science and Scopus, a citation analysis was conducted on 8,652 English language journal articles published in 2007-2015. Citation Content Analysis (CCA) for syntactic and semantic analysis of contents, developed by Guo Zhang, Ying Ding and Staša Milojević CCA was also performed on single-authored articles of Filipino faculty members published in 2007-2015. The results of this study can yield valuable insights on how Filipino researchers cite sources which may be used for library collection development.